2004
DOI: 10.1002/ijc.20373
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of IL‐17 in cutaneous T‐cell lymphomas (mycosis fungoides and sezary syndrome)

Abstract: Interleukin-17 (IL-17) is a proinflammatory cytokine mainly produced by activated CD4 ؉ CD45RO T cells. In mice, we have demonstrated that, depending on the model, IL-17 may act as a tumor growth-promoting or -inhibiting factor. In order to address the relevance of these models in human tumors, we look for the natural expression and activity of IL-17 in mycosis fungoides (MF) and Sezary syndrome (SS). These cutaneous T-cell lymphomas were selected because they are usually CD3 ؉ CD4 ؉ CD45RO ؉ , a phenotype sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 45 publications
6
90
2
1
Order By: Relevance
“…haematopoietic tumours in immunocompetent mice) [112,113] of tumours in experimental animals. Although the role of IL-17 in tumour biology is unclear and evidence remains conflicting, IL-17 can be detected in some (such as ovarian, skin and prostatic cancers) [114][115][116] but not all (e.g. acute myeloid leukaemia) [117] human tumours and one emerging theme is that, when present, it promotes angiogenesis [111,114], for example through the up-regulation of angiogenic factors such as CXCL1, CXCL5, CXCL6 and CXCL8 [118], thereby facilitating tumour growth and invasion.…”
Section: Systemic Lupus Erythematosis (Sle) and Other Conditionsmentioning
confidence: 99%
“…haematopoietic tumours in immunocompetent mice) [112,113] of tumours in experimental animals. Although the role of IL-17 in tumour biology is unclear and evidence remains conflicting, IL-17 can be detected in some (such as ovarian, skin and prostatic cancers) [114][115][116] but not all (e.g. acute myeloid leukaemia) [117] human tumours and one emerging theme is that, when present, it promotes angiogenesis [111,114], for example through the up-regulation of angiogenic factors such as CXCL1, CXCL5, CXCL6 and CXCL8 [118], thereby facilitating tumour growth and invasion.…”
Section: Systemic Lupus Erythematosis (Sle) and Other Conditionsmentioning
confidence: 99%
“…1 T-cell differentiation that is predominant in the skin lesions of MF patients, [13][14][15][16][17] it has been consistently reported that the percentage of forkhead box P3 positive (FoxP3 1 ) cells decreases with disease progression.…”
Section: Mycosis Fungoides (Mf) Is the Most Common Clinical Variant Omentioning
confidence: 99%
“…Previous reports have shown that both cutaneous T-cell lymphomas 6 and ovarian carcinomas 7 spontaneously secrete interleukin (IL)-17A and in a considerable proportion of ovarian tumours IL-17A expression correlates with increased vascularity. However, no report exists concerning a possible angiogenic role for IL-17A in non-small cell lung cancer (NSCLC) [8][9][10] .…”
mentioning
confidence: 99%